Experimental investigation on the effectiveness of 1-butyl-3- methylimidazolium perchlorate ionic liquid as a reducing agent for heavy oil upgrading - Md. Saaid, I. (American Chemical Society, 2014)
An ionic liquid (IL), 1-butyl-3-methylimidazolium perchlorate, BMIMClO4, is synthesized and used as a reducing agent to upgrade a selected heavy oil. The effects of BMIMClO4 on viscosity, density, SARA contents, elemental compositions, and molecular weight of the heavy oil are studied. The results show that the heavy oil treated with BMIMClO4 has reduction in viscosity and density. The results also indicate that the presence of BMIMClO4 significantly changes the composition of the heavy oil. Moreover, the effects of BMIMClO4 on the interfacial tension (IFT) of oil-water and oil recovery are tested. Results shows that BMIMClO4 can improve the mobility of heavy oil by reducing the IFT of oil-water and increase the recovery factor by 79.94%. Â© 2014 American Chemical Society.